Correlação entre uso de circulação extracorpórea, Tempo de internação e complicações pulmonares pós-revascularização do miocárdio - Rocha, Gabriel Mauriz de Moura (2012)
Cardiovascular diseases are among the leading causes of death in developed countries and coronary artery bypass grafting is an effective procedure for treating coronary artery disease. Objective: To determine the characteristics (gender) and to correlate the use of cardiopulmonary bypass, with the length of stay and pulmonary complications. Methodology: Cross-sectional study of a quantitative nature, performed at two hospitals in the month of November 2010. We analyzed 30 charts (15 of 15 private hospitals and the charity hospital), the data being analyzed: gender, a previous diseases, use and duration of cardiopulmonary bypass, pulmonary complications. Results: In relation to gender was male predominance in 53%. From the records analyzed, only one (1) of the patients involved did not use cardiopulmonary bypass and the maximum usage time was 230 minutes. The main pulmonary complication observed was pleural effusion and more incidents of predisposing factors were diabetes mellitus and hypertension. Conclusion: We conclude that patients undergoing coronary artery bypass grafting surgery with the presence of cardiopulmonary bypass have different respiratory function changes, which affect the length of stay and in pulmonary complications. However, this study lacks statistical power and has some biases that prevent this claim solid.